Access to asylum : international refugee law and the globalisation of migration control - Gammeltoft-Hansen, Thomas (Cambridge, New York : Cambridge University Press, 2013)
"Is there still a right to seek asylum in a globalised world? Migration control has increasingly moved to the high seas or the territory of transit and origin countries, and is now commonly outsourced to private actors. Under threat of financial penalties airlines today reject any passenger not in possession of a valid visa, and private contractors are used to run detention centres and operate border crossings. In this volume Thomas Gammeltoft-Hansen examines the impact of these new practices on refugees' access to asylum. A systematic analysis is provided of the reach and limits of international refugee law when migration control is carried out extraterritorially or by non-state actors. State practice from around the globe and case law from all the major human rights institutions are discussed. The arguments are further linked to wider debates in the fields of human rights, general international law and political science"--Provided by publisher
1. Introduction -- 2. The refugee and te globalisation of migration control -- 3. Refugee protection and the reach of the non-refoulement principle -- 4. Offshore migration control and the concept of extraterritorial jurisdiction -- 5. The privatisation of migration control and state responsibility -- 6. 'Hic abundant leones' : the institutional reach of refugee protection -- 7. Conclusion
"Table of cases : xv-xix"
First paperback edition published 2013
First published 2011
Includes bibliographical references (p. 249-269) and index
Keywords: Asylum, Right of; Law and globalization; Political refugees -- Legal status, laws, etc